A Causal Factors Model Inflf luencing Consumer Loyalty toward AliExpress Application of China in Thailand - คำสุข แววมยุรา; กำแพงเพชร มรกต; ภู่เผือก อาภรณ์; ศิวเวชช ปรียา; เพ็งจันทร์ พัฒนพงศ์; ฮาตระวัง ฉัตรแก้ว (Business Administration and Management Journal Review, 2019)
The purpose of this research was to study the factors influencing of the variable needs of consumer loyalty of AliExpress application use and to develop a model of factors that influence the loyalty of consumers using AliExpress application express in Thailand. The research instrument was a questionnaire to collect data from 400 consumers who using AliExpress application. Results indicated that the structure (Structure Equation model: SEM) showed Customer Satisfaction and the Perceive Value had a direct positive influence on Consumer Loyalty. Furthermore, the Perceive Quality had an indirect positive influence on Consumer Loyalty toward Customer Satisfaction and Perceive Value. The final model can explain the Loyalty of Consumers with 74 percent (R2 = 0.74).